Photography in brazilian teaching journalism speech in the first half of the 20th century (Research, Society and Development, 2021)
Through the theoretical-methodological proposal of Archaeological Discourse Analysis, by the French philosopher Michael Foucault (2005), the work focuses on the discourse of six pedagogical intentions for the teaching of journalism that emerged in the first half of the last century, between 2018 and 1950. In them, we seek to identify the discursive place occupied by photography, through the analysis tools offered by Discourse Archeology. Six curricular intentions from this period that precede the officialization of higher education courses in journalism in Brazil are analyzed, which only occurred in 1950. Access to these documents was given through the work of Dias (2018), who carried out a survey about the origins of journalism education in the country. Even though most of these curricula have not come into operation, they demonstrate that photography was already understood as something important for study in journalism since 1918, in opposition to what is stated in the current National Curriculum Guidelines for journalism courses, published in 2013, which left photography out of its lines.